Instalasi Automatic Valve Drain Sand Trap Tank Pabrik Kelapa Sawit - Dona Tiara Lubis (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2023)
In the collecting oil process at the clarification station the sand trap tank process is first, the trapped sand will be blown down or drained by the operator to reduce NOS (Non Oil Soiled) levels. With the installation of an automatic drain valve, this will further increase the performance of quality control at the clarification station and also minimize maintenance costs for the clarification machines. Another goal is regularity of the drain sand trap tank, affecting the stages of the refining and collecting oil process. Oil separation in the VCT (Vertical Clarifier Tank) with a norm of 40% oil, 40% water and 20% NOS will be maximally achieved, due to the NOS in the sand trap tank improving the blow down results.